Pseudoknot length modulates the folding, conformational dynamics, and robustness of Xrn1 resistance of flaviviral xrRNAs - Niu, Xiaolin; Sun, Ruirui; Chen, Zhifeng; Yao, Yirong; Zuo, Xiaobing; Chen, Chunlai; Fang, Xianyang (Nature communications, 2021)
To understand how RNA dynamics is regulated and connected to its function, we investigate the folding, conformational dynamics and robustness of Xrn1 resistance of a set of flaviviral xrRNAs using SAXS, smFRET and in vitro enzymatic assays. Flaviviral xrRNAs form discrete ring-like 3D structures, in which the length of a conserved long-range pseudoknot (PK2) ranges from 2 bp to 7 bp. We find that xrRNAs’ folding, conformational dynamics and Xrn1 resistance are strongly correlated and highly Mg 2+ -dependent, furthermore, the Mg 2+ -dependence is modulated by PK2 length variations. xrRNAs with long PK2 require less Mg 2+ to stabilize their folding, exhibit reduced conformational dynamics and strong Xrn1 resistance even at low Mg 2+ , and tolerate mutations at key tertiary motifs at high Mg 2+ , which generally are destructive to xrRNAs with short PK2. These results demonstrate an unusual regulatory mechanism of RNA dynamics providing insights into the functions and future biomedical applications of xrRNAs. Exoribonuclease-resistant RNAs (xrRNAs) are RNA elements that block the exoribonucleolytic degradation of RNA. Here the authors show how a long-range pseudoknot length modulates the Mg 2+ -dependence of flaviviral xrRNA’s folding, conformational dynamics and Xrn1 resistance.